Digital image of the city as a form of communication - Tormakhova, Anastasiia (Ukrainian Cultural Studies, 2022)
Historically, the city is the center where the main vectors of human life are concentrated. In particular, the modern city can be presented through the prism of the media. The city currently exists not only as a certain objective reality, but also as a result of reflection on the life events of its inhabitants. The practice of separating citizens in real terms is compensated by the creation of virtual media communication centers. The whole set of communication about the city can be connected to different types of information portals, open for viewing social networks and closed groups for internal communication. The analysis of the results of photo fixation of locations in different temporal characteristics was an attempt to understand the specifics of fluctuations in digital content. It also vividly demonstrated that the city acquires a different character in cyberspace. Cyberspace acts as a new tool for cartography of urban space. According to a number of researchers, the complex structure of the city becomes clear only in it. The definition of a person’s place in the modern city is automatically related to a certain delineation of his place in information flows. Media and cyberspace become a locus of urban collective memory. This is due to the fact that modern cities are undergoing significant changes. However, this happens so quickly that there is a spatial and temporal gap between the memory and the perception of the real urban space. The image of modern cities is formed in the media space, which is often focused on creating an attractive image of the city, which may not be too true to reality. Daily and festive (or those that do not fit into the everyday) events are reflected in media sources. They record the process of changes in the urban space. At the same time, cyberspace also contains past images of the city. The multi-layered visual image of the city in media sources leads to the formation of the phenomenon of discontinuity of temporal and spatial features. The memory of the city and its real appearance coexist in the network, generating a new image of it.